Fierce bliss [compact disc] - Wilson, Ann, 1950- (Silver Lining Music, 2022)
Heart's Ann Wilson creates a supremely lavish, warm, and seductive slice of rock n' roll that provides an instant soundtrack whether on the freeway or in front of the fireplace.